2010
DOI: 10.4193/rhino10.069
|View full text |Cite
|
Sign up to set email alerts
|

Symptom score questionnaire for nasolacrimal duct obstruction in adults--a novel tool to assess the outcome after endoscopic dacryocystorhinostomy

Abstract: BACKGROUND: The incidence of nasolacrimal pathway obstruction increases with age, and dacryocystorhinostomy (DCR) is a commonly applied surgical technique to treat severe cases. However, no disease-specific tools to assess the symptoms and the subjective outcome after DCR have been established. We have developed a specific Nasolacrimal Duct Obstruction Symptom Score (NLDO-SS) questionnaire to evaluate the outcome, and tested it in a prospective clinical trial. STUDY DESIGN: Prospective clinical follow-up study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…In the literature there are two questionnaires not translated or validated in Italian, the Lac-Q (Lacrimal symptom questionary) and the NLDO-SS (Nasolacrimal duct obstruction-symptom score), designed to evaluate the success of the DCR intervention [ 13 , 14 ]. Although they are more specific for the symptoms resulting from obstructive tear pathology, the GBI can evaluate both the symptoms due to the disease and the psychological and social features.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are two questionnaires not translated or validated in Italian, the Lac-Q (Lacrimal symptom questionary) and the NLDO-SS (Nasolacrimal duct obstruction-symptom score), designed to evaluate the success of the DCR intervention [ 13 , 14 ]. Although they are more specific for the symptoms resulting from obstructive tear pathology, the GBI can evaluate both the symptoms due to the disease and the psychological and social features.…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, we decided to employ NLDO-SS to assess patient satisfaction after an anatomically and surgically successful CDCR procedure. NLDO-SS was originally conceived by Smirnov et al 5 to assess outcomes after treatment naso-lacrimal duct obstructions, and we decided to apply the score to our patients since nasolacrimal duct obstruction and canalicular obstruction share the same plethora of symptoms 14 , and both the anatomical subsites participate as a whole to the lacrimal drainage system. NLDO-SS is not the only tool available to assess postsurgical QoL: Glasgow Benefit Inventory (GBI) and Lacrimal Symptoms Questionnaire (Lac-Q) are also widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were guided through the questionnaire by the interviewer. The NLDO-SS questionnaire 5 consists of five items focusing on the common ocular symptoms of NLDO: tearing, discharge in the eye, swelling around the eye, pain around the eye, change in visual acuity; along with two items describing the conditions in the nasal cavity: nose blockage, nasal cavity discharge (Tab. I).…”
Section: Nldo-ss Questionnairementioning
confidence: 99%
“…[3][4][5][6][7][8][9] Ramey et al performed a systematic review of outcome measures reported by all oculoplastic patients and were able to identify only two validated lacrimal surgery questionnaires, the Nasolacrimal Duct Obstruction Symptom Score (NLDO-SS) and the Lac-Q questionnaire, both of which are speci c to DCR surgery. [10][11][12] Therefore, this prospective study aimed to investigate the changes in tear meniscus parameters following external DCR surgery in patient with NLDO. Additionally, we assessed the association between these changes and improvements in quality of life outcomes.…”
Section: Introductionmentioning
confidence: 99%